Clinical, haematological and biochemical profiling of podoconiosis lymphoedema patients prior to their involvement in a clinical trial in the Northwest Region of Cameroon. (1st December 2020) - Ndzeshang, Bertrand Lontum; Mbiakop, Randy Tchachoua; Nchanji, Gordon Takop; Kien, Chi Anizette; Amambo, Glory Ngongeh; Abong, Raphael Awah; Yuyun, Timothy; Beng, Amuam Andrew; Bonekeh, John; Ritter, Manuel; Esum, Mathias Eyong; Cho, Jerome Fru; et al.
Abstract: Background: Prior to carrying out clinical trials, it is important to assess the health status of the study participants to be able to interpret subsequent changes that may be related to the effects of the treatments during the follow-up of patients. This study presents the clinical, haematological and biochemical profiles of podoconiosis patients prior to their involvement in the PodoLEDoxy clinical trial. Methods: All lower limb lymphoedema patients visiting the centre were screened and a podoconiosis diagnosis was based on clinical manifestation and detailed medical history. Patients who satisfied the eligibility criteria were enrolled in the study and their demographic data, vital signs and medical history were collected followed by biochemical and haematological examinations. Results: Of the 222 participants enrolled in the study, 55.4% and 41.4% had either stage 3 or 2 podoconiosis as their highest stages, respectively. On physical examination, gastritis (46%) and poor vision (2.7%) were the most prevalent health issues identified. The majority of haematological and biochemical values were within the normal range except for mean platelet volume (47.7%), plateletcrit (58.1%), platelet distribution width (66.2%), mean corpuscular volume (67.6%) and red cell distribution width-standard deviation (79.3%), where >40% of the study participants had values out of the normal. Conclusion: The clinical, haematological and biochemical profiles of the study participants were largely within the normal range except for certain haematological parameters that might be worth investigating.